HGC: HyperGraph based Clustering scheme for power aware wireless sensor networks - Gbadouissa, Jocelyn Edinio Zacko; Ari, Ado Adamou Abba; Titouna, Chafiq; Gueroui, Abdelhak Mourad; Thiare, Ousmane (Elsevier, 2019)
Due to the energy constraints of sensors owing to the limitation of their built-in batteries, the lifespan of Wireless Sensor Networks (WSNs) are significantly affected. These particular ad-hoc networks have a huge number of applications including surveillance and target tracking. Unfortunately, since sensor nodes are limited in terms of power resources, efficient utilization of these resources is an important goal to design power-aware WSNs. This led researchers to propose numerous methods, such as clustered WSNs, in order to effectively manage the power resources. In this work, we proposed a heuristic clustering based on the hypergraph theory, and called HyperGraph Clustering (HGC) that aims at optimizing the energy of sensor nodes. Theoretical evaluation highlighted that this clustering protocol consumed less energy during the cluster formation phase and the selection of the cluster head. In addition, we evaluated the performance of the proposed HGC and the results showed the effectiveness of our scheme to those we compared in terms of the number of nodes alive, residual energy and the total consumption of the network.
With the recent advances of Micro Electro Mechanical Systems, especially in semiconductors’ technologies that led to the design of smart sensors, networking, and material science technologies have enabled a significant shift in Wireless Sensor Network (WSN) [1, 2].
Keywords: Clustering; Wireless Sensor Networks; Hypergraph modelling; Simulation